Curcumin Loaded Polymeric vs. Lipid Nanoparticles: Antioxidant Effect on Normal and Hypoxic Olfactory Ensheathing Cells - Angela Bonaccorso; Rosalia Pellitteri; Barbara Ruozi; Carmelo Puglia; Debora Santonocito; Rosario Pignatello; Teresa Musumeci (Nanomaterials, 2021)
Background: Curcumin (Cur) shows anti-inflammatory and antioxidant effects on central nervous system diseases. The aim of this study was to develop Cur-loaded polymeric and lipid nanoparticles for intranasal delivery to enhance its stability and increase antioxidant effect on olfactory ensheathing cells (OECs). Methods: The nanosuspensions were subjected to physico-chemical and technological evaluation through photon correlation spectroscopy (PCS), differential scanning calorimetry (DSC) and UV-spectrophotometry. The cytotoxicity studies of nanosuspensions were carried out on OECs. A viability test was performed after 24 h of exposure of OECs to unloaded and curcumin-loaded nanosuspensions. The potential protective effect of Cur was assessed on hypoxic OECs cells. Uptake studies were performed on the same cell cultures. Thermal analysis was performed to evaluate potential interaction of Cur with a 1,2-Dimyristoyl-sn-glycero-3-phosphocholine (DMPC) biomembrane model. Results: PCS analysis indicated that lipid and polymeric nanosuspensions showed a mean size of 127.10 and 338.20 nm, respectively, high homogeneity and negative zeta potential. Incorporation of Cur into both nanocarriers increased drug stability up to 135 days in cryoprotected freeze-dried nanosuspensions. Cell viability was improved when hypoxic OECs were treated with Cur-loaded polymeric and lipid nanosuspensions compared with the control. Conclusions: Both nanocarriers could improve the stability of Cur as demonstrated by technological studies. Biological studies revealed that both nanocarriers could be used to deliver Cur by intranasal administration for brain targeting.